CUSTOMER PERSPECTIVE ANALYSIS OF E-COMMERCE INFORMATION SYSTEMS IN TOKOPEDIA - Raditya Hendra Pratama; Khoirunnisa Khoirunnisa (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
The development of technology and information systems has made e-commerce a daily transaction space. Business actors have begun to pay great attention to their customers within e-commerce to maintain sustainability and profit for their businesses. For this reason, it is important how the customer's perception of the service in the revenue cycle is carried out, and this is in line with the concept balanced scorecard which makes the customer-aspect as one of the important aspects outside of the financial aspect. This study uses a case study on Tokopedia as one of the largest marketplaces in Indonesia to find out how customers perceive the services presented in Tokopedia’s system as part of the revenue cycle in the accounting information system. From this study we found that although there were some obstacles from the perspective of some customers, the overall system built by Tokopedia was able to gain a good perception from most of its customers.